The Effectiveness of Podcast-Based Listening Learning Media for 9th Grade Students of SMP N 5 Jepara - Andriawan, Andra; Rosdiana, Aliva; Mahalli (Journal of English Language and Pedagogy (JELPA), 2024)
This study aims to determine the significant differences and effectiveness of podcasts on the listening skills of 9th grade students of SMP N 5 Jepara in the academic year 2022/2023. The researcher used a quasi-experimental design involving 30 students of 9H as the experimental class and 30 students of 9G as the control class. Data was collected using a listening test instrument consisting of pre-test and post-test. Then, the sampling technique used by the researcher was purposive sampling in which the sample was not taken at random. Furthermore, data analysis used SPSS statistical calculations. The results showed that the average post-test score for the experimental class was higher than the control class (86.9 > 78.9). This indicated that there was a significant difference in the post-test results. Then, the results of the hypothesis analysis showed that t observe was higher than table, namely (4,176 > 2,000). In addition, the 2 tailed sig was lower than alpha (0.00 < 0.05). This means that H0 is rejected and Ha is accepted. These results showed significant differences in the use of podcasts for students' listening skills. Besides that, podcast was also effectively used for listening learning.